Analisis Penurunan Timbunan Tanah Silt Pada Proyek Jalan Ruas Giriwoyo-Duwet Wonogiri - Agung Prakoso; Muhammad Mukhlisin; Junaidi Junaidi; Pentardi Rahardjo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2019)
The foundation layers of road construction in general have many problems of land subsidence. Land subsidence does not occur only on the ground or the original soil. Decrease of soil may also occur on pile or soil. Less than optimal density of the soil or the choice of unsuitable heap material may be the cause of the land subsidence in the embankment. Land subsidence also occurred in the National Road Development Project Segment Giriwoyo-Duwet, Wonogiri, Central Java, Indonesia, causing a decrease in road elevation from planned elevations. Decreasing this elevation can cause the standards of the cleverness and comfort of the road not being met. This study explains the results of the analysis of the large decrease in soil that occurred. The analysis is done by two methods. The method is done by theoretical calculation and by analysis using plaxis software. The results of the analysis show that the characteristics of soil used as soil pile material is silt soil with high and soft plasticity characteristics. The analysis also illustrates the factors of land degradation due to poor soil characteristics, carrying capacity and soil density less than standard and weather factors. The magnitude of the decline that occurred showed a decrease of 3-7 cm from the observation on the location, 1,1 cm from the results of plaxis software analysis and 1,7 cm from theoretical calculations.